A fresh look at Cosmetus Perty, 1833 (Opiliones: Cosmetidae), with new synonymies and description of two new species from Colombia - Medrano, Miguel; Kury, Adriano B.; Martinez, Leonel (Zootaxa, 2021)
Cosmetus Perty, 1833 is the type genus of the most diverse subfamily of Laniatores, Cosmetinae. The genus currently includes 22 valid species with a disconnected distribution, including coastal forests of NE Brazil, dry forests of the Ecuadorian Pacific, Chocó-Darien moist forests and the Venezuelan Andes. The morphology among species in the genus is quite variable, but they share almost exclusively the fused spine in area III. The type species Cosmetus varius is little known due to few, poor quality illustrations, a vague type locality, and lost type material, and was misidentified by Koch in 1840, making it difficult to define or even taxonomically revise the genus. Herein we: (1) provide distribution maps for nominal Cosmetus species; (2) recognize the poorly defined type species C. varius as a species occurring in central-eastern Bahia, agreeing with the itinerary of Spix and von Martius; (3) synonymize three other species from central-eastern Bahia with C. varius; (4) provide images of the external morphology of three Brazilian species of the genus; and (5) describe two new sympatric species from the Colombian Pacific region (Chocó-Darien moist forest), thus representing the first report of the genus for the country. Both Colombian species, Cosmetus acanti sp. nov. and Cosmetus villarreali sp. nov., have similar external morphology but are remarkably different in genital morphology. Morphological evidence indicates that Cosmetus may be an artificial group. However, given the chaotic taxonomy of the family Cosmetidae, and the deep intertwining of nomenclature, we do not know at the moment where each of those species should be classified.